The utilization of template matching method for license plate recognition - A. Jalil, Norazira; Hasan Basari, Abd Samad; Salam, Sazilah; Ibrahim, Nuzulha Khilwani (Praise Worthy Prize, 2014)
License plate detection and recognition system has been an active research domain in image processing field. However, these systems are less accurate due to different styles of car plates endorsed and yet there are still unable to reach the high accuracy in recognition. Thus, the aim of this research is to develop an automated method of determining the best recognition performance based on Malaysia license plate vehicle registration number. Towards achieving this aim, a database of characters and license plate image has been created by collecting images from various type of car. The initial pre-processing involves image enhancement, binarization and followed by filtering and segmenting license plate. Template matching method is used to recognize the characters, from A-Y and 0-9, using standard Malaysia license plate font which is Arial. There are 100 license plates that contain 693 characters have been tested, and the result shown that 92.78% of all characters is correctly recognized. Thus, template matching can be classified as one of the best algorithm for recognizing Malaysia license plate.